BANTUAN HUKUM TIMBAL BALIK DALAM TINDAK PIDANA NARKOTIKA - Yogi Arthani, Ni Luh Gede; Andayani Citra, Made Emy (Institut Hindu Dharma Negeri Denpasar, 2021)
Ilicit Traffic in Narcotic Drugs is carried out by international networks operating in several countries. Ilicit traffic in narcotic drugs results in huge financial and wealth gains that enable transnational crime organizations to penetrate, pollute and undermine the structure of government, legitimate commercial and financial business, and society at all levels. In dealing with this situation, Indonesia harmonizes the law through mutual legal assistance arrangements. In this study two issues will be discussed namely legal reform through mutual legal assistance and mutual legal assistance in narcotics crimes.Legal reform is a policy carried out by a country to deal with the situation that occurs in the country. The development of transnational crime was responded by the state through a policy of mutual legal assistance as outlined in the Law of the Republic of Indonesia Number 1 of 2006 concerning Reciprocal Assistance in Criminal Matters. Cooperation between countries in the process of law enforcement needs to be done to tackle the crime of trafficking in narcotics. Ilicit traffic in narcotic drugs is carried out by involving several countries. Reciprocal legal assistance in narcotics crimes can be implemented in three ways, namely diplomatic channels, through central authorities and through direct cooperation between law enforcement agencies.Keywords: Mutual legal assistance, Ilicit Traffic, Narcotic Drugs